2003
DOI: 10.1016/s0010-0277(02)00232-9
|View full text |Cite
|
Sign up to set email alerts
|

Alphabetic and nonalphabetic L1 effects in English word identification: a comparison of Korean and Chinese English L2 learners

Abstract: Different writing systems in the world select different units of spoken language for mapping. Do these writing system differences influence how first language (L1) literacy experiences affect cognitive processes in learning to read a second language (L2)? Two groups of college students who were learning to read English as a second language (ESL) were examined for their relative reliance on phonological and orthographic processing in English word identification: Korean students with an alphabetic L1 literacy ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
148
1
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 282 publications
(189 citation statements)
references
References 40 publications
19
148
1
1
Order By: Relevance
“…There are several studies in the literature that confirm the transfer of linguistic skills between different languages, from Arabic to English (Abu-Rabia & Siegel, 2002;Al-Tamimi & Rabab'ah, 2007), from Hebrew to English (Geva & Siegel 2000), from English to French (Deacon, Wade-Woolley, & Kirby, 2009), from Russian to English (Abu-Rabia & Sanitsky, 2010), from Spanish to English (Ramí rez, Chen, Geva, & Kiefer, 2010), from Persian to English (Nassaji and Geva, 1999), from Chinese to English (Wang, Koda, & Perfetti, 2003). Those studies documented that skills like vocabulary and syntactic awareness or phonological skills can be transferred from one language to another.…”
Section: Research Findings On the Linguistic Skills Transfer Between mentioning
confidence: 98%
“…There are several studies in the literature that confirm the transfer of linguistic skills between different languages, from Arabic to English (Abu-Rabia & Siegel, 2002;Al-Tamimi & Rabab'ah, 2007), from Hebrew to English (Geva & Siegel 2000), from English to French (Deacon, Wade-Woolley, & Kirby, 2009), from Russian to English (Abu-Rabia & Sanitsky, 2010), from Spanish to English (Ramí rez, Chen, Geva, & Kiefer, 2010), from Persian to English (Nassaji and Geva, 1999), from Chinese to English (Wang, Koda, & Perfetti, 2003). Those studies documented that skills like vocabulary and syntactic awareness or phonological skills can be transferred from one language to another.…”
Section: Research Findings On the Linguistic Skills Transfer Between mentioning
confidence: 98%
“…For example, Wang, Koda, and Perfetti (2003) found differences between Korean and Chinese learners of English as a second language in the degree to which they committed false alarms to phonological foils (sale) in an English semantic judgment task (part of a boat: sail). learners made more such errors and Chinese learners made them only when the foil shared most of its letters with the target.)…”
Section: If Writing Fits Language What Are the Implications For Readmentioning
confidence: 99%
“…Research has also suggested that language-specific differences are related to differences in processing skills and strategies in reading (Akamatsu, 2003;Bang & Zhao, 2007;Chen, 1992;Fender, 2003;Hayes-Harb, 2006;Koda, 1988Koda, , 1989Koda, , 2005Wang & Koda, 2007;Wang, Koda, & Perfetti, 2003). For example, when Koda (1988Koda ( , 1989) compared the cognitive strategies of ESL readers from four L1 orthographic backgrounds, she found that when reading in English, the readers used cognitive strategies developed in their L1.…”
Section: The Effects Of Linguistic Differences On Readingmentioning
confidence: 99%